Estimation of Some Useful Drugs in Water, Urine, and Medical Formulations Following Conventional and Modified Dispersive Microextraction Coupled with HPLC-UV - Sarkar, Mitali; Denrah , Shanku (Sustainable Chemical Engineering, 2021)
Dispersive Liquid-Liquid Microextraction (DLLME) coupled with high-performance liquid chromatography-ultraviolet spectroscopy was developed, as a fast and precise operation, for extractive recovery and estimation of two pharmaceuticals, viz. moxifloxacin and galantamine, from water, urine, and medical formulations. The process was investigated for extraction solvent (ES) and dispersive solvent (DS), as well as pH, temperature, and salt concentration. Extraction was found effective using methanol (CH3OH) as the DS, employing 1, 1, 2, 2-tetrachloroethane (C2H2Cl4) and chloroform (CHCl3) as the ES for moxifloxacin and galantamine, respectively. The optimum pH was found to be 6.9 for moxifloxacin and 10.2 for galantamine. Temperature and salt were found to have some influence on the extraction efficiency of moxifloxacin but were insignificant for galantamine. An improvement of the operation in terms of extraction efficiency (ER%), preconcentration factor (PF), thermodynamic feasibility, and greenness was achieved during surfactant-aided DLLME (SDS-DLLME), where an anionic surfactant (sodium dodecyl sulphate (SDS)) was employed and no DS was required. Interestingly, the volume requirement for ES was found to be less compared to that in conventional DLLME, without compromising the performance. Moreover, quantitative recovery of both drugs was achieved using a single ES. Thus, mutual separation and simultaneous determination of moxifloxacin and galantamine may be designed. A two-phase separation with concomitant enrichment of the solute in the sediment phase occurred. The drugs in the sediment phase, on subsequent dilution with methanol, were determined using the high-performance liquid chromatography-ultraviolet (HPLC-UV) system. The negative free energy changes for the operation indicated that the process was thermodynamically feasible. The process was found to be effective for the spiked recovery of the studied drugs from real samples, viz., water, human urine, and commercial medical formulations.